Sustainable Rural Development Perspective and Global Challenges - Özçatalbaş, Orhan (IntechOpen, 2023)
Agriculture is vitally important to humanity. Climate change, environmental pollution, global warming, and the COVID-19 pandemic have highlighted the importance of food safety and food security. This book discusses sustainable agriculture and its importance in combatting the adverse effects of climate change and meeting the world's food demand. And essentially the technologies to be used for CE to prevent climate change should be "common property of humanity". This may be a new paradigm, but the real issue is the future of the earth and ensuring the continuity of sustainable life. It is a fact that the creation of such a culture of sharing will serve all the SDGs put forward by the UN.